A Study on Epidemiological Profile of Urinary Tract Infections in Perspective of Diabetic Status among Patients Attending Tertiary Care Hospital, Ahmedabad - Viral R Dave; Venu R Shah; K N Sonaliya; Shruti D Shah; Aniruddha R Gohel (Medsci Publications, 2018)
Background Urinary Tract Infection (UTI) is common illness in- volving all age groups. Diabetics tend to have more episodes of illness as compared to non diabetics. Present study compared various epidemiological aspects of UTI among diabetic and non diabetic patients. Methods: A hospital based study was conducted among 300 cases (200 non diabetics and 100 diabetics) of UTI attending one of the tertiary care hospitals of Ahmedabad city. Bacterial Isolation and antimicrobial sensitivity was tested in urine samples of all cases. Z test, Chi-square test with Cramers' V and Phi correlation were ap- plied for testing the statistical significance. Result: Mean age of diabetics and non-diabetics was 55.6 ± 12.1 years and 33.7 ± 21.9 years, respectively.UTI cases with positive urinary culture were 92% and 67% in diabetic and non-diabetic groups, respectively. Most common organism isolated among both the groups was E coli. In both groups E coli and Klebsiella had high antimicrobial sensitivity for Imipenam, Gentamycin and Nitrofu- rantoin. Among diabetics, the duration of diabetes, regularity of medication and type of treatment has significant effect on number of episodes of UTI in a year. Conclusion: Escherichia coli were universally common isolate. Aminoglycoside and Nitrofurantoin can still be used empirically to treat UTI irrespective of diabetic status. Screening of urine sam- ples for antimicrobial sensitivity while initiating the course of treatment among all UTI cases is recommended to check for and prevent resistance.